2021
DOI: 10.1186/s12889-021-10867-w
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use in medical cannabis authorization adult patients from 2013 to 2018: Alberta, Canada

Abstract: Background The opioid overdose epidemic in Canada and the United States has become a public health crisis - with exponential increases in opioid-related morbidity and mortality. Recently, there has been an increasing body of evidence focusing on the opioid-sparing effects of medical cannabis use (reduction of opioid use and reliance), and medical cannabis as a potential alternative treatment for chronic pain. The objective of this study is to assess the effect of medical cannabis authorization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…For example, pain was one of the highest conditions noted where medical cannabis is being used in this cohort of patients. We have previously shown that cannabis may have important impacts to help reduce the use of opioids for chronic pain at the population level [ 35 ]. Thus, medical cannabis authorization could be a potential strategy to minimize harm associated with opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pain was one of the highest conditions noted where medical cannabis is being used in this cohort of patients. We have previously shown that cannabis may have important impacts to help reduce the use of opioids for chronic pain at the population level [ 35 ]. Thus, medical cannabis authorization could be a potential strategy to minimize harm associated with opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Six observational studies (N=12,939) reported on the effects of cannabis, with five (3 high, 2 moderate risk of bias) studies evaluating medical cannabis programs, [62][63][64] or self-reported use of cannabis, 65,66 and one moderate risk of bias study evaluating a specific whole-plant cannabis product. 61 Patient characteristics are summarized across studies in Table 5.…”
Section: Summary Of Findings For Whole-plant Cannabis and Mixed (Pati...mentioning
confidence: 99%
“…One study evaluated outcomes at 3 months (short duration), 64 and the other five were long duration (1 to 4 years observation). [61][62][63]65,66 The three studies of medical cannabis programs allowed patients to self-select the cannabis products they used and compared them with patients who chose not to enroll in the programs (assumed to be no cannabis use). [61][62][63] Two of the studies are retrospective analyses of larger prospective cohort studies of patients with chronic pain taking opioids, 65,66 based on patient self-report of cannabis use, but specific products used were not reported.…”
Section: Summary Of Findings For Whole-plant Cannabis and Mixed (Pati...mentioning
confidence: 99%
See 2 more Smart Citations